Numerical study of nano-encapsulated phase change material micropolar fluid flow in a thermal energy storage system with a rotating cylinder - Rashed, Z.Z.; Ahmed, Sameh E. (Maǧallaẗ al-abḥath al-handasiyyaẗ, 2025)
This study examines the micropolar fluid flow of nano-encapsulated phase change materials (NEPCMs) within an irregular star-shaped thermal energy storage system (TESS). The flow domain incorporates rotating or stationary cylinders, subject to either heating or cooling, across four configurations: (1) a rotating, inner-heated cylinder with cold outer boundaries, (2) a stationary, inner-heated cylinder with cold outer boundaries, (3) a rotating, cold inner cylinder with heated outer boundaries, and (4) a stationary, cold inner cylinder with heated outer boundaries. The host fluid is a red blood cell (RBC) suspension, while the NEPCM core and shell are composed of nonadecane and polyurethane, respectively. An aluminum foam matrix serves as the porous medium, and the system is modeled using the local thermal non-equilibrium (LTNE) approach. A novel numerical framework, based on the Finite Volume Method (FVM), is developed to solve the governing equations. The MATLAB inpolygon function is applied to precisely capture the irregular domain and its boundaries. Heat transfer in both the fluid and solid phases, as well as the overall heat transfer around the inner cylinder, is visualized through polar plots and optimized using response surface methodology (RSM). Results show that the Nusselt number around the cylinder increases with higher amplitude values. Moreover, the micropolar fluid exhibits significantly enhanced thermal activity in the configuration with a rotating cylinder and heated outer boundaries. Overall, the results demonstrate that the combination of NEPCMs and micropolar fluids in irregular geometries provides a versatile approach to optimize thermal performance in energy storage systems and biomedical applications.